Two new species of Sarothrogammarus (Crustacea, Amphipoda) from Swat Valley, Pakistan - Xin, Wenpei; Zhang, Chao; Ali, Abid; Zhang, Xiaoqing; Li, Shuqiang; Hou, Zhonge (Zootaxa, 2024)
Two new species of the genus Sarothrogammarus Martynov, 1935 are described and illustrated from Pakistan. Sarothrogammarus miandamensis sp. nov. is characterized by the oval eyes; pereopod III having filtrative setae on merus, carpus and propodus; uropod III terminal article distinct and inner ramus scale-shaped; and having robust setae and slender setae on urosomites I–III. Sarothrogammarus kalamensis sp. nov. can be distinguished from the above species by pereopod III having filtrative setae on merus, but few on carpus and propodus. Detailed morphological characteristics, as well as comparisons with closely related species are provided. Molecular phylogenetic analyses suggest that S. miandamensis sp. nov. is clustered with S. kalamensis sp. nov., with a genetic distance of 19% for COI between the two species.